Asphalt densified carbon-carbon composite material and preparation method thereof

Through vacuum-assisted high-pressure impregnation and covering polyurea and thermosetting adhesives, the problem of poor density-enhancing carbon-carbon composite materials is solved, and more efficient density-enhancing and more uniform material structure is achieved, reducing production costs .

CN119462190AActive Publication Date: 2025-02-18CHENGDU CARBON

Patent Information

Application Number
CN202411596572.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-18
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

The prior art uses asphalt to perform density enhancement treatment of carbon-carbon composite materials, and the density enhancement effect is poor, and the production cost is high, making it difficult to control material uniformity and stability.

Method used

The asphalt is impregnated by vacuum-assisted high-pressure, followed by covering polyurea and thermoset high-temperature resistant adhesive, forming a stable high-temperature resistant continuous shell, preventing the asphalt from flowing out, and forming a high-density carbon-carbon composite material in the high-temperature graphitization treatment.

Benefits of technology

The density-enhancing efficiency of asphalt density carbon-carbon composite materials, the uniformity and stability of product quality and structure are significantly improved, and production costs are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462190A_ABST
    Figure CN119462190A_ABST
Patent Text Reader

Abstract

The invention discloses an asphalt densified carbon-carbon composite material and a preparation method thereof. Belongs to the technical field of carbon-carbon composite materials. The preparation method comprises the following steps: carrying out asphalt high-pressure impregnation on a carbon fiber preform or a low-density carbon-carbon composite material, sequentially carrying out polyurea covering and curing and thermosetting high-temperature-resistant adhesive covering and curing on the non-placement surface of the impregnated material, and then carrying out heating carbonization and high-temperature graphitization treatment. According to the invention, the densification efficiency when the asphalt is used for densifying the carbon-carbon composite material, the quality of the obtained product and the uniformity and stability of the structure can be obviously improved, and the production cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of carbon-carbon composite materials, and in particular to a method for preparing a carbon-carbon composite material by densifying asphalt. Background Art

[0002] Asphalt is widely available, inexpensive, has a high residual carbon rate after high temperature, and the asphalt carbon obtained after carbonization has a higher degree of graphitization than the pyrolytic carbon obtained by pyrolysis or the resin carbon obtained by resin carbonization. It is increasingly used in the preparation of carbon-carbon composites, especially in the density enhancement treatment of carbon-carbon composites, that is, densification treatment.

[0003] At present, when using asphalt to densify carbon-carbon composite materials, in order to ensure the densification effect, the asphalt is often chemically modified or the unmodified asphalt is impregnated with high temperature and high pressure. However, in the above methods, the chemical modification method has high cost and low production efficiency, and the modified material is difficult to reuse; and when high temperature and high pressure impregnation is used, because the physical properties of asphalt are similar to thermoplastic resins, when the temperature is higher than the softening point of asphalt, the viscosity of asphalt decreases rapidly with the increase of temperature, which will cause most of the impregnated asphalt in the preform or carbon-carbon composite material to flow out during the carbonization process, resulting in poor densification effect. In order to improve this problem, some existing technical means have further adopted the method of repeating the asphalt impregnation and carbonization process many times, but this method significantly increases the production cost, reduces the structural and performance uniformity of the material, and increases the difficulty of controlling the stability of material quality. Summary of the invention

[0004] In order to solve the above-mentioned problems of the prior art, the purpose of the present invention is to provide a new method for preparing carbon-carbon composite materials by asphalt densification, which can significantly improve the densification efficiency when using asphalt to densify carbon-carbon composite materials and the quality, structural uniformity and stability of the obtained products, thereby reducing production costs.

[0005] The technical solution of the present invention is as follows:

[0006] A method for preparing an asphalt-densified carbon-carbon composite material, comprising:

[0007] (1) impregnating a carbon fiber preform or a low-density carbon-carbon composite material with asphalt, wherein the impregnation method is vacuum-assisted high-pressure impregnation, to obtain a first composite material;

[0008] (2) using one outer surface of the first composite material as a placement surface, using polyurea to cover all surfaces of the first composite material except the placement surface, and obtaining a second composite material after curing;

[0009] (3) further covering all surfaces of the second composite material covered with polyurea with a thermosetting high temperature resistant adhesive to obtain a third composite material;

[0010] (4) placing the surface of the third composite material horizontally downward, and then heating it until the thermosetting high temperature resistant adhesive is completely cured to obtain a fourth composite material;

[0011] (5) placing the fourth composite material with its surface facing upward, and then heating and carbonizing it in an inert atmosphere to obtain a fifth composite material;

[0012] (6) The fifth composite material is subjected to high-temperature graphitization treatment to obtain a pitch-densified carbon-carbon composite material.

[0013] In the above technical solution of the present invention, polyurea is first covered on part of the surface of the asphalt-impregnated carbon fiber preform or porous carbon-carbon composite material, and then covered with a thermosetting high-temperature resistant adhesive, wherein polyurea can significantly improve the bonding strength and covering quality between the thermosetting high-temperature resistant adhesive and asphalt, and the processing efficiency is high. After the polyurea is combined with the thermosetting high-temperature resistant adhesive, a stable continuous shell resistant to 450°C can be formed on the asphalt surface, effectively preventing the outflow of asphalt during the carbonization stage, improving the asphalt use efficiency and carbon yield, and at the same time, polyurea and thermosetting high-temperature resistant adhesives only retain carbon elements after carbonization and high-temperature graphitization, and no physical removal or chemical purification is required.

[0014] According to some preferred embodiments of the present invention, the preparation method further comprises: performing a density test on the composite material obtained by the heating and carbonization, and if the density reaches the set requirement, performing the high temperature graphitization treatment, otherwise, repeating steps (1) to (5) several times until the density reaches the set requirement.

[0015] According to some preferred embodiments of the present invention, the asphalt is selected from one or more of high-temperature coal tar pitch, mesophase asphalt and modified coal tar pitch having a softening point of 80 to 180°C.

[0016] According to some preferred embodiments of the present invention, the density of the carbon fiber preform is 0.10-0.60 g / cm 3 .

[0017] According to some preferred embodiments of the present invention, the density of the low-density carbon-carbon composite material is 0.6-1.4 g / cm 3 .

[0018] According to some preferred embodiments of the present invention, the immersion temperature is 200-300° C., and the immersion pressure is 2.0-5.0 MPa.

[0019] According to some preferred embodiments of the present invention, the thermosetting high temperature resistant adhesive comprises a thermosetting resin, and the thermosetting resin is selected from phenolic resin and / or furan resin.

[0020] According to some preferred embodiments of the present invention, the thermosetting high temperature resistant adhesive further comprises a modifier and a diluent, the modifier is selected from high temperature coal tar powder and / or mesophase coal tar powder, and the diluent is selected from methanol and / or ethanol.

[0021] According to some preferred embodiments of the present invention, in the thermosetting high temperature resistant adhesive, the mass ratio of the thermosetting resin, the modifier and the diluent is 100:(2-10):(0-25).

[0022] According to some preferred embodiments of the present invention, the covering thickness of the polyurea is 0.05-0.2 mm.

[0023] According to some preferred embodiments of the present invention, the covering thickness of the thermosetting high temperature resistant adhesive is 0.6 to 1.5 mm.

[0024] According to some preferred embodiments of the present invention, the temperature of the carbonization treatment is 800-1000°C, and the heating rate in the heating range of 400°C-450°C is ≤10°C / h.

[0025] According to some preferred embodiments of the present invention, the temperature of the high temperature graphitization treatment is 1800-2500°C.

[0026] The present invention further provides a carbon-carbon composite material densified by asphalt prepared according to the above preparation method. The density of the composite material is 1.3-1.8 g / cm 3 .

[0027] The present invention can significantly reduce the number of asphalt impregnation and carbonization cycles in the traditional asphalt impregnation densification method, save asphalt usage, reduce production energy consumption and carbon emissions, and obtain a densified carbon-carbon composite material with more uniform internal and external density. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 SEM images of the interior (a) and edge (b) of the densified flat carbon-carbon composite material obtained in Example 1;

[0029] Figure 2 This is a physical picture of the carbon-ceramic brake disc of the carbon-carbon composite material obtained in Example 4;

[0030] Figure 3 These are SEM images of the interior (a) and edge (b) of the densified carbon-carbon composite material obtained in Comparative Example 1. DETAILED DESCRIPTION

[0031] The technical scheme of the present invention will be further described below in conjunction with the embodiments and drawings of the present invention. The embodiments described below are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0032] Example 1

[0033] The densified flat carbon-carbon composite material is prepared in batches by the following steps:

[0034] (1) The volume density is 0.40 g / cm 3 The flat carbon fiber preform is subjected to asphalt vacuum-assisted high-pressure impregnation to obtain a composite material A, wherein the impregnation pressure is 2.0 MPa, the impregnation temperature is 210° C., the asphalt is high-temperature coal tar pitch with a softening point of 108° C. to 120° C., the quinoline insoluble matter content thereof is ≤4.0%, and the coking value is ≥54%;

[0035] (2) Using one horizontal surface of composite material A as the placement surface, using Alxincai D460 polyurea primer to roll-coat polyurea on all surfaces of composite material A except the placement surface, and placing the coated material in a 50° C. forced air oven for 15 min and then taking it out to obtain composite material B;

[0036] (3) Applying a thermosetting phenolic adhesive twice on the entire surface of the composite material B on which the polyurea primer had been sprayed, with each application having a scraping thickness of 0.3 to 0.5 mm, to obtain a composite material C; wherein the thermosetting phenolic adhesive is Shandong Shengquan The PF9501B thermosetting high-viscosity phenolic resin is prepared by adding 6% by mass of 200-mesh high-temperature asphalt powder and 12% by mass of ethanol and mixing them evenly;

[0037] (4) placing the composite material C with its surface facing downward in a forced air drying oven and treating it at 200° C. for 2 h to obtain composite material D;

[0038] (5) placing the composite material D with its placement surface facing upward into a carbonization furnace, heating it to 900° C. and carbonizing it for 4 h, wherein the heating rate between 400° C. and 450° C. is 6.5° C. / h, to obtain a composite material E;

[0039] (6) The composite material E was graphitized at 2100°C for 3 h to obtain a densified flat carbon-carbon composite material.

[0040] The volume density of the densified flat carbon-carbon composite material is 0.82-0.90 g / cm 3 The average volume density is 0.86 g / cm 3The charcoal yield was 48-53%, and the average charcoal yield was 51.1%.

[0041] The microstructure of the densified flat carbon-carbon composite material was characterized. The SEM images of the interior (a) and edge (b) of the obtained material are shown in the attached figure. Figure 1 As shown, it can be seen that inside the carbon-carbon composite material, the asphalt is stacked in layers between the carbon fiber fibers in the form of sheets, and the gaps between the fibers have been basically filled with asphalt; at the edge of the carbon-carbon composite material, most of the gaps between the fibers in the SEM field of view are also filled with asphalt, with only a few isolated carbon fibers at the very edge.

[0042] Example 2

[0043] The densified flat carbon-carbon composite material is prepared by the following steps:

[0044] (1) The volume density is 0.45 g / cm 3 The flat carbon fiber preform is subjected to asphalt vacuum-assisted high-pressure impregnation to obtain a composite material A, wherein the impregnation pressure is 3.6 MPa, the impregnation temperature is 230° C., the asphalt used is a modified impregnated coal tar pitch with a softening point of 105 to 115° C., and the quinoline insoluble content thereof is ≤2.0% and the coking value is ≥50%;

[0045] (2) Using a horizontal surface of composite material A as the placement surface, spraying all surfaces of composite material A to be densified except the placement surface with Langke WXPUA-901 high temperature and wear-resistant polyurea twice, and naturally curing to obtain composite material B;

[0046] (3) Roll-coating the entire surface of the composite material B coated with the polyurea primer three times with a furan adhesive, each time with a thickness of 0.2 to 0.3 mm, to obtain a composite material C; wherein the furan adhesive is obtained by adding 15% by mass of high-temperature coal tar powder with an average particle size of 150 mesh to the furan resin of Huibo;

[0047] (4) placing the composite material C with its surface facing downward into a carbonization furnace and treating it at 220° C. for 3 h to obtain composite material D;

[0048] (5) With the surface facing upward, the composite material D is turned over on the upper and lower surfaces, and the temperature is raised to 850° C. for carbonization treatment for 4 h, wherein the heating rate between 400° C. and 450° C. is 5° C. / h, to obtain a composite material E;

[0049] (6) treating the composite material E as the flat carbon fiber preform of step (1), and repeating steps (1) to (4) three times;

[0050] (7) The treated composite material obtained in step (6) is graphitized at 2400° C. for 2 h to obtain a densified flat carbon-carbon composite material.

[0051] The volume density of the densified flat carbon-carbon composite material was 1.65 g / cm 3 .

[0052] Example 3

[0053] The heat insulation cylinder for thermal field of carbon-carbon composite material is prepared by the following steps:

[0054] (1) The volume density of the natural gas obtained by chemical vapor infiltration (CVI) is about 0.90 g / cm 3 Carbon-carbon composite insulation tube;

[0055] (2) performing vacuum-assisted high-pressure impregnation of medium-temperature asphalt on the obtained carbon-carbon composite insulation cylinder to obtain a composite insulation cylinder A, wherein the impregnation temperature is 240° C., the impregnation pressure is 1.6 MPa, and the medium-temperature asphalt used is a high-purity impregnation low-ash asphalt of the Lu coal system, and its softening point is 80° C. to 95° C.;

[0056] (3) Using the 1 / 6 outer circumferential arc surface of the composite material insulation tube A as the placement surface, using the Aier New Materials D460 polyurea primer roller to coat the entire surface of the composite material insulation tube A except the placement surface with polyurea, and after natural surface drying, obtaining the composite material insulation tube B;

[0057] (4) High-temperature adhesive was roller-coated twice on the entire surface of the composite material insulation tube B on which the polyurea primer had been sprayed, with each roller coating thickness of 0.2 to 0.3 mm, to obtain a composite material insulation tube C; wherein the high-temperature adhesive was Yushiju PF-YSJ-2180M phenolic resin powder, which was dissolved in 20 wt % ethanol and then added with 10 wt % of high-temperature asphalt powder with an average particle size of 400 meshes and mixed evenly;

[0058] (5) With its placement surface facing downward, the composite material insulation cylinder C is placed on a curved wooden tooling in a forced air drying oven and treated at 160° C. for 4 h to obtain a composite material insulation cylinder D;

[0059] (6) With its placement surface facing upward, the composite material insulation tube D is placed on a curved steel tooling in a carbonization furnace, nitrogen is introduced, and the temperature is raised to 1000° C. for carbonization treatment for 2.5 hours, wherein the heating rate between 400° C. and 450° C. is 4° C. / h; thereby obtaining a composite material insulation tube E;

[0060] (7) The composite material insulation tube E is treated at a high temperature of 2300°C for 3 hours to obtain a carbon-carbon composite material insulation tube for hot field.

[0061] According to the test, the volume density of the carbon-carbon composite material of the thermal insulation tube for the thermal field is not less than 1.25g / cm 3 .

[0062] Example 4

[0063] The carbon-ceramic brake disc of the carbon-carbon composite material is prepared by the following steps:

[0064] (1) The bulk density obtained by natural gas CVI densification treatment is about 1.0 g / cm 3 The carbon-carbon composite disc;

[0065] (2) performing vacuum-assisted high-pressure impregnation of mesophase pitch on the obtained carbon-carbon composite disc to obtain a composite disc A, wherein the impregnation temperature is 280° C., the impregnation pressure is 2.0 MPa, and the asphalt used is Baowu mesophase pitch MP-1, and its softening point is 155° C. to 175° C.;

[0066] (3) Using any disk plane of the composite material disk A as the placement surface, using Langke WXPUA-901 high temperature and wear-resistant polyurea to coat the entire surface of the composite material disk A except the placement surface with polyurea twice, and obtaining the composite material disk B after natural curing;

[0067] (4) Spraying the entire surface of the composite material disk B with the polyurea primer for 3 to 5 times with a thermosetting boron phenolic adhesive to a total thickness of about 1.2 mm to obtain a composite material C; wherein the thermosetting boron phenolic adhesive is Shandong Shengquan PF9506 ablation-resistant boron phenolic resin is prepared by adding 5% by mass of 400-mesh mesophase asphalt powder and 6% by mass of methanol and mixing them uniformly;

[0068] (5) With its surface facing downward, the composite material disc C is placed in a forced air drying oven and heated to 180° C. for 2 h to obtain a composite material disc D;

[0069] (6) With its placement surface facing upward, the composite material disc D is placed in a carbonization furnace, nitrogen is introduced, and the temperature is raised to 900° C. for carbonization treatment for 3 h, wherein the heating rate between 400° C. and 450° C. is 5° C. / h; thereby obtaining a composite material disc E;

[0070] (7) treating the composite material disc E as the carbon-carbon composite material disc in step (2), and repeating the processes of steps (2) to (6) once;

[0071] (8) The treated composite material disk obtained in step (7) was treated at 2100° C. for 3.5 h to obtain the following Figure 2 The carbon-ceramic brake disc shown uses a carbon-carbon composite material.

[0072] From the attached Figure 2 It can be seen that the black carbon is densely filled and evenly distributed in the entire carbon-carbon composite disk, and there is no CVI densification block on the surface. Furthermore, 9 Φ30*30 cylinders were cut on the carbon-carbon composite disk. After testing, the average volume density was about 1.45g / cm3, and the coefficient of variation was ≤3%; the average open porosity was about 19%, and the coefficient of variation was ≤2%.

[0073] Comparative Example

[0074] The densified flat carbon-carbon composite material is prepared in batches by the following steps:

[0075] (1) The volume density is 0.40 g / cm 3 The flat carbon fiber preform is subjected to asphalt vacuum-assisted high-pressure impregnation to obtain a composite material A, wherein the impregnation pressure is 2.0 MPa, the impregnation temperature is 210° C., the asphalt is high-temperature coal tar pitch with a softening point of 108° C. to 120° C., the quinoline insoluble matter content thereof is ≤4.0%, and the coking value is ≥54%;

[0076] (2) placing composite material A into a carbonization furnace, introducing nitrogen, heating to 900°C for carbonization treatment for 4 hours, wherein the heating rate between 400°C and 450°C is 6.5°C / h, and obtaining composite material B;

[0077] (3) The composite material B is graphitized at 2100°C for 3 h to obtain a densified flat carbon-carbon composite material.

[0078] The volume density of the densified flat carbon-carbon composite material is 0.73-0.78 g / cm 3 , the average volume density is 0.72g / cm 3 The charcoal yield was 40-43%, and the average charcoal yield was 41.6%.

[0079] It can be seen that Comparative Example 1 used the same preform, asphalt and impregnation, carbonization and high-temperature graphitization treatment processes as Example 1, but the average density of the densified flat carbon-carbon composite material obtained in Example 1 was increased by 19.4%, and the average carbon yield was increased by 22.8%.

[0080] Furthermore, the microstructure of the densified flat carbon-carbon composite material was characterized. The SEM images of the interior (a) and edge (b) of the obtained material are shown in the attached figure. Figure 3 As shown, it can be seen that inside the carbon-carbon composite material, the gaps between the single fibers are also basically filled with asphalt, but the filling rate is worse than that of Example 1; at the edge of the carbon-carbon composite material, almost no asphalt filling is seen in the SEM field of view, and almost all of them are exposed carbon fibers. The asphalt at the edge of the carbon-carbon composite material is almost completely lost during the carbonization process.

[0081] It should be noted that the above is only a preferred embodiment of the present invention, which should not limit the protection scope of the technical solution of the present invention. Any modification of the technical solution recorded in the above embodiments and equivalent replacement of technical features by ordinary technicians in the field within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a carbon-carbon composite material densified by asphalt, characterized in that: It includes: (1) impregnating a carbon fiber preform or a low-density carbon-carbon composite material with asphalt, wherein the impregnation method is vacuum-assisted high-pressure impregnation, to obtain a first composite material; (2) using one outer surface of the first composite material as a placement surface, using polyurea to cover all surfaces of the first composite material except the placement surface, and obtaining a second composite material after curing; (3) further covering all surfaces of the second composite material covered with polyurea with a thermosetting high temperature resistant adhesive to obtain a third composite material; (4) placing the surface of the third composite material horizontally downward, and then heating it until the thermosetting high temperature resistant adhesive is completely cured to obtain a fourth composite material; (5) placing the fourth composite material with its surface facing upward, and then heating and carbonizing it in an inert atmosphere to obtain a fifth composite material; (6) The fifth composite material is subjected to high-temperature graphitization treatment to obtain a pitch-densified carbon-carbon composite material.

2. The preparation method according to claim 1, characterized in that: The method further comprises: performing a density test on the composite material obtained by the heating and carbonization, and if the density reaches the set requirement, performing the high-temperature graphitization treatment; otherwise, repeating steps (1) to (5) several times until the density reaches the set requirement.

3. The preparation method according to claim 1, characterized in that: in, The asphalt is selected from one or more of high-temperature coal tar pitch, mesophase asphalt and modified coal tar pitch with a softening point of 80 to 180° C.; and / or the density of the carbon fiber preform is 0.10 to 0.60 g / cm 3 ; and / or, the density of the low-density carbon-carbon composite material is 0.6 to 1.4 g / cm 3 .

4. The preparation method according to claim 1, characterized in that: The immersion temperature is 200-300° C., and the immersion pressure is 2.0-5.0 MPa.

5. The preparation method according to claim 1, characterized in that: The thermosetting high temperature resistant adhesive comprises a thermosetting resin, and the thermosetting resin is selected from phenolic resin and / or furan resin.

6. The preparation method according to claim 5, characterized in that: The thermosetting high temperature resistant adhesive further comprises a modifier and a diluent, wherein the modifier is selected from high temperature coal tar powder and / or mesophase coal tar powder, and the diluent is selected from methanol and / or ethanol.

7. The preparation method according to claim 6, characterized in that: In the thermosetting high temperature resistant adhesive, the mass ratio of the thermosetting resin, the modifier and the diluent is 100:(2-10):(0-25).

8. The preparation method according to claim 1, characterized in that: The polyurea has a covering thickness of 0.05 to 0.2 mm; and / or the thermosetting high temperature resistant adhesive has a covering thickness of 0.6 to 1.5 mm.

9. The preparation method according to claim 1, characterized in that: The temperature of the carbonization treatment is 800-1000°C, and the heating rate in the heating range of 400°C-450°C is ≤10°C / h; and / or the temperature of the high-temperature graphitization treatment is 1800-2500°C.

10. A pitch-densified carbon-carbon composite material prepared by the preparation method according to any one of claims 1-9.

Citation Information

Patent Citations

  • Pitch-based carbon fiber non-woven felt heat-insulating cylinder and preparation method thereof

    CN104261853A

  • Preparation method of one-dimensional high-thermal-conductivity C / C composite material

    CN114436669A

  • Densification carbon-carbon composite material and densification method thereof

    CN118005416A

  • Asphalt carbon foamed material preparation method

    CN1733603A

  • Ceramic impregnated superabrasives

    US20060042171A1

Cited By

  • Preparation method of short-process isostatic pressing high-strength graphite

    CN120964794A

  • A Short-Process Isostatic Pressing Method for Preparing High-Strength Graphite

    CN120964794B